Brief history of syphilis - Tampa, M; Sarbu, I; Matei, C; Benea, V; Georgescu, S R (Journal of medicine and life, 2014)
Before the discovery of Treponema pallidum as the etiologic agent, the origins of syphilis have been the subject of several debates. Diverse therapeutic agents were employed in an attempt to cure the disease. Examining the milestones in the history of syphilis, the present article reviews the existing theories that tried to explain the origins of the disease, the approach in art, the cultural and the evolution of the treatments from the empiric means to the discovery of penicillin.